Gene mutations in squamous cell NSCLC: insignificance of EGFR, KRAS and PIK3CA mutations in prediction of EGFR-TKI treatment efficacy - Fiala, Ondrej; Pesek, Milos; Finek, Jindrich; Benesova, Lucie; Bortlicek, Zbynek; Minarik, Marek (Anticancer research, 2013)
BACKGROUND: Epidermal growth factor receptor (EGFR), Kirsten rat sarcoma viral oncogene (KRAS) and phosphatidylinositide-3-kinase catalytic subunit-alpha (PIK3CA) mutations are biomarkers used for the prediction of efficacy of EGFR tyrosine kinase inhibitors (EGFR-TKIs) in advanced non-small cell lung cancer (NSCLC). PATIENTS AND METHODS: In total, 223 patients with advanced-stage squamous cell NSCLC were tested; 179 patients were treated with EGFR-TKIs. Genetic testing was performed using a combination of denaturing capillary electrophoresis and direct Sanger sequencing. RESULTS: EGFR mutations were detected in 7.2%; KRAS mutations in 7.4% and PIK3CA mutations in 3.8% of patients. No correlation of EGFR or PIK3CA mutation status with progression-free survival (PFS) (p=0.425; p=0.197), nor overall survival (OS) (p=0.673; p=0.687), was observed. KRAS mutations correlated with shorter OS (p=0.039), but not with PFS (p=0.120). CONCLUSION: We did not observe any role of EGFR, KRAS, PIK3CA mutations in prediction of EGFR-TKIs efficacy in patients with advanced-stage squamous cell NSCLC.
Keywords: nádory plic; nemalobuněčný karcinom plic; Lung Neoplasms; Humans; inhibitory proteinkinas; lidé středního věku; Carcinoma, Non-Small-Cell Lung; Phosphatidylinositol 3-Kinases; ErbB Receptors; Female; mutace; Aged; dospělí; ras Proteins; senioři; lidé; chemorezistence; protoonkogenní proteiny p21(ras); Class I Phosphatidylinositol 3-Kinases; erbB receptory; protoonkogenní proteiny; Adult; Protein Kinase Inhibitors; staging nádorů; Follow-Up Studies; ženské pohlaví; Male; Middle Aged; Proto-Oncogene Proteins p21(ras); Retrospective Studies; fosfatidylinositol-3-kinasy; prognóza; Aged, 80 and over; Proto-Oncogene Proteins; fosfatidylinositol-3-kinasy třídy I; Ras proteiny; senioři nad 80 let; spinocelulární karcinom; retrospektivní studie; Carcinoma, Squamous Cell; Neoplasm Staging; míra přežití; Mutation; mužské pohlaví; Drug Resistance, Neoplasm; Prognosis; následné studie; Survival Rate